A solid phase reaction liquid marble type semiconductor wafer grinding block and its preparation method and application
Through the combination of liquid marble and magnetic particles of liquid marble grinding blocks, the problem of inconsistent abrasive particle distribution in SiC wafer grinding is solved, and efficient grinding of multiple semiconductor wafers is achieved, and the grinding effect is improved. efficiency and reduce pollution.
Patent Information
- Application Number
- CN202211084919.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-06
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-09-06
AI Technical Summary
The orientation distribution of existing solid-phase reaction grinding discs is inconsistent in SiC wafer grinding, resulting in poor consistency of grinding effect and narrow application range, making it impossible to effectively process common semiconductor wafers such as diamond, silicon carbide and other materials.
Liquid marble-type grinding blocks are adopted, including abrasives, binders and liquid marbles. The liquid marbles are composed of hydrophobic nanomagnetic particles. Through the directional arrangement of magnetic fields, combined with reaction liquid and lubricating liquid, the directional distribution of abrasives and grinding efficiency are improved. , a uniform pit structure is formed to enhance self-sharpness.
It improves the consistency and efficiency of the grinding effect, extends the service life of the grinding disc, reduces pollution and waste, and can effectively process a variety of semiconductor wafer materials.
Smart Images

Figure CN115533738B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor wafer precision machining, and in particular to a solid-phase reaction liquid marble-type semiconductor wafer grinding block and a preparation method and application thereof. Background Art
[0002] With the rapid development of microelectronics technology, humans have higher requirements for the overall or local flatness of semiconductor wafers, the local flatness of the front side (nanotopology), surface roughness and other technical indicators. The surface roughness is required to reach the nanometer level, and the shape error is required to reach the submicron level. Semiconductor wafers are the basic raw materials for manufacturing semiconductor devices. High-purity semiconductors are prepared into semiconductor wafers through processes such as crystal pulling and slicing. Semiconductor wafers with corrosion resistance, wear resistance, and chemical stability are then processed through a series of semiconductor manufacturing processes to form tiny circuit structures. After cutting, packaging, and testing, they finally become chips, which are widely used in electronic technology, microelectronics technology, and micro-electromechanical technology. However, semiconductor wafers generally have the characteristics of high hardness and high brittleness. Cracks and sub-surface damage are easily generated during the processing process, which seriously affects the surface processing quality.
[0003] Among the current ultra-precision processing technologies for semiconductor wafers, chemical mechanical polishing (CMP) is the most mature. Semiconductor wafers processed by this technology can obtain good surface roughness. However, chemical mechanical polishing also has problems such as uncontrollable free abrasive trajectory, poor post-processing shape accuracy, and a large amount of polishing waste liquid generated during the processing process, which will cause serious pollution to the environment if not properly handled. In view of the problems existing in chemical mechanical polishing of semiconductor wafers, fixed abrasive tools (grinding wheels, grinding discs, polishing pads) based on the principle of solid-phase reaction are used to process semiconductor wafers. The advantages include controllable machining abrasive trajectory, high post-polishing shape accuracy, and no polishing waste liquid generation. However, fixed abrasive tools have small chip space that is easy to clog and wear, poor self-sharpening, random distribution of abrasive particles, and difficulty in ensuring the consistency of polishing effects.
[0004] The prior art discloses a solid phase reaction grinding disc for grinding SiC wafers, wherein a mixture containing abrasive grains, ferromagnetic particles, hydrogen peroxide capsules and a resin binder is placed under magnetic field conditions, and the ferromagnetic particles entrain the abrasive grains and hydrogen peroxide capsules to be arranged in a directional manner along the direction of the magnetic field lines, and the grinding disc obtained after curing has better strength, hardness and good grinding and polishing performance. However, the uniform arrangement of the abrasive grains in the grinding disc described in the prior art relies on the ferromagnetic particles driving the abrasive grains to achieve directional arrangement under magnetic field conditions, but the magnetic particles also drive the directional arrangement of the hydrogen peroxide capsules at the same time, so in some defective parts of the wafer, the abrasive grains and hydrogen peroxide capsules cannot be arranged regularly in some areas, resulting in the problem that the consistency of the SiC wafer grinding effect is not strong, thereby affecting the grinding and polishing effect of the SiC wafer. In addition, the solid phase reaction grinding disc described in the prior art is only used in the grinding and polishing of SiC wafers. For the grinding and polishing of common semiconductor wafers such as diamond, silicon carbide, sapphire, gallium nitride, indium phosphide, and gallium arsenide, the prior art does not mention the relevant processing methods. Summary of the invention
[0005] The present invention provides a solid phase reaction liquid marble type semiconductor wafer grinding block to overcome the problems of the solid phase reaction grinding disk in the prior art that the directional distribution of abrasive grains needs to be improved and the application range of the grinding disk is narrow.
[0006] Another object of the present invention is to provide a method for preparing a liquid marble-type semiconductor wafer grinding block by solid phase reaction.
[0007] Another object of the present invention is to provide a solid phase reaction liquid marble type semiconductor wafer grinding disk.
[0008] Another object of the present invention is to provide the application of the solid phase reaction liquid marble type semiconductor wafer grinding disk in semiconductor wafer grinding and polishing.
[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0010] The grinding disc of the present invention is composed of a base disc and a grinding block bonded to the base disc.
[0011] A solid phase reaction grinding block, comprising the following components in parts by weight: 15 to 35 parts of abrasive, 45 to 60 parts of a binder, and 15 to 25 parts of liquid marbles; the grinding block also comprises pores distributed inside the grinding block; the liquid marbles and the abrasive in the grinding block are directionally arranged in the binder; the abrasive particle size is 0.2 μm to 30 μm, the liquid marble particle size is 10 μm to 5 mm, and the liquid marble particle size is ≧20 times the abrasive particle size; the liquid marbles comprise a core and an outer wall; the outer wall of the liquid marbles is composed of hydrophobic nano-magnetic particles, and the core is liquid; the liquid marbles comprise a first liquid marble whose core liquid is a reaction liquid that can undergo a solid phase reaction with the abrasive and a second liquid marble whose core liquid is a lubricating liquid; the mass ratio of the first liquid marble to the second liquid marble is 0.1 to 10.
[0012] The solid phase reaction grinding block of the present invention is composed of abrasive, binder and liquid marbles; the outer wall of the liquid marbles is hydrophobic nano-magnetic particles, and the liquid marbles include a first liquid marble whose core liquid is a reaction liquid that can react with the abrasive in a solid phase and a second liquid marble whose core liquid is a lubricating liquid. The outer wall of the liquid marbles can make the liquid marbles have a certain strength, ensuring that the marbles do not break during the mixing process, and the hydrophobic nano-magnetic particles on the outer wall of the liquid marbles can be directed and distributed under the action of magnetic induction lines by applying a magnetic field during the solidification process of the solid phase reaction grinding disk, so that the abrasive is clamped and pushed by the liquid marbles and distributed in a directed manner, thereby improving the consistency of the grinding effect. During the grinding process of semiconductor wafers, the abrasive particles, liquid marbles in the grinding block and the surface of the object being ground react with each other to form a passivation layer due to friction. At this time, the liquid marbles arranged in a direction near the abrasive are broken under the action of mechanical force, and the liquid inside is gradually released. The reaction liquid accelerates the solid-phase reaction rate, and the lubricating liquid makes the grinding more uniform. The reaction liquid and the lubricating liquid together provide a liquid environment for the solid-phase reaction and accelerate the solid-phase reaction rate. While the liquid marbles are broken, countless uniform and dense pits are formed on the surface of the grinding disc. These pits and the bubbles in the grinding block can both play the role of accommodating chips. In addition, the presence of the pits accelerates the shedding of the abrasive particles and improves the self-sharpening of the solid-phase reaction grinding disc.
[0013] The strength of the liquid marbles of the present invention means that when the prepared liquid marbles freely fall from a height of 30 mm and hit a glass plate at a speed of 0.8 m / s, the liquid marbles do not break.
[0014] The pores of the present invention account for 5% to 15% of the volume of the grinding block.
[0015] The abrasive material of the present invention is a soft abrasive material or a hard abrasive material.
[0016] Preferably, the soft abrasive of the present invention is one or more of silicon dioxide, cerium oxide, and silica sol, and the hard abrasive is one or more of diamond, silicon carbide, and aluminum oxide.
[0017] Preferably, the abrasive particles of the present invention have a particle size of 0.2 to 15 μm.
[0018] According to the present invention, when rough grinding the wafer, a hard abrasive of 14 μm to 30 μm should be selected; when fine grinding the wafer, a soft abrasive of less than 14 μm should be selected.
[0019] The binder of the present invention is one or more of a phenolic resin binder, a polyimide resin binder, an epoxy resin binder, and a magnesium oxychloride binder.
[0020] The hydrophobic nano magnetic particles of the present invention are one or more of ferroferric oxide, carbonyl iron powder, nickel oxide, manganese ferrite, cobalt ferrite and nickel ferrite magnetic powder.
[0021] The reaction liquid of the present invention is one or more of a magnesium fluoride solution, a boron oxide solution, a Fenton reaction liquid, an electro-Fenton reaction liquid, and an ultraviolet photocatalytic reaction liquid.
[0022] In the Fenton reaction liquid system of the present invention, Fe3O4 is ionized under acidic conditions to produce Fe 2+ and Fe 3+ , oxidant H2O2 and Fe 2+ The Fenton reaction generates a strong oxidant ·OH, which promotes the solid phase reaction between the abrasive particles, liquid marbles in the grinding block and the surface of the ground object; adding an external electric field to the Fenton reaction (i.e., the electric Fenton reaction) can enable the reaction system to produce ·OH continuously, stably and controllably.
[0023] The ultraviolet photocatalytic reaction liquid of the present invention is composed of hydrogen peroxide and titanium dioxide particles. When the nano-TiO2 is irradiated with ultraviolet light of a certain wavelength (lower than 387.5nm), the positively charged holes can react with H2O2 and OH adsorbed on the surface of the TiO2 particles. - Oxidation reaction occurs to generate OH with strong oxidizing property, which promotes the solid phase reaction between abrasive grains, liquid marbles and the surface of the object being ground.
[0024] The lubricating fluid of the present invention is one or more of deionized water, emulsion, gasoline, turbine oil and glycerin.
[0025] Preferably, the concentration of the reaction solution of the present invention is 1 to 30%wt.
[0026] The present invention also protects a method for preparing a solid phase reaction grinding block, comprising the following steps:
[0027] S1. Add the reaction liquid and the lubricating liquid dropwise onto the hydrophobic nanomagnetic particle layer, saturate the hydrophobic nanomagnetic particles and wrap them on the droplets to form liquid marbles on the droplets;
[0028] S2. Mix the ground, sieved, and dried abrasives, binders, and liquid marbles prepared in S1 in proportion, inject into a mold placed on an ultrasonic vibration platform, and stir the mixture at a uniform speed to form pores; after the mixture is injected, apply magnetic fields and pressure to the upper and lower surfaces of the mold in sequence, with a magnetic field strength of 20 to 800 mT to orient the magnetic liquid marbles, and a pressure of 50 to 1000 N. During the curing process, the ambient temperature is maintained at 15 to 25°C, the curing time is 12 to 168 hours, and the abrasive block is demolded after being cured at room temperature.
[0029] S1 In the process of preparing liquid marbles, the reaction liquid and the lubricating liquid are preferably added dropwise to the hydrophobic nanomagnetic particle layer respectively, and the hydrophobic nanomagnetic particles are wrapped on the droplets by rolling back and forth to form liquid marbles. The nanoparticles will automatically coat the surface of the liquid marbles during the rolling process. After the surface of the droplets is saturated with nanoparticles and completely covered, the liquid marbles are prepared. At this time, even if rolling is applied again, the nanoparticles will not coat the liquid marbles.
[0030] During the stirring process of S2, the speed should not be too fast, as too fast a speed may cause the liquid marbles to break; therefore, the stirring of S2 should avoid this situation. The stirring can be carried out by any known method, such as manual stirring, mechanical stirring, etc. When using a mechanical stirrer, it is preferably controlled at a lower speed, as long as the liquid marbles are not broken. The stirring is used together with ultrasound to disperse the abrasives that are easy to agglomerate, and the resulting mixture is more uniform. At the same time, during the stirring process of injecting the mixture in S2, since the binder and other materials are viscous, air will be brought in during the stirring process, forming pores in the grinding block, which plays a role in heat conduction and accommodating grinding chips during the grinding of the crystal sheet. The initial state of the binder is flowing. When the mixture is still in a flowing state, a magnetic field is applied to direct the liquid marbles to arrange them in a directional manner, so that the abrasive is clamped and pushed by the liquid marbles, making the abrasive arrangement more regular, and the pressure is applied to solidify and shape, thereby improving the consistency of the grinding effect.
[0031] Preferably, the stirring time is 20 to 30 minutes.
[0032] The present invention also protects a solid phase reaction grinding disc, including a grinding block prepared by the above preparation method.
[0033] Preferably, the solid phase reaction grinding disc of the present invention comprises a base disc and a grinding block prepared by the above preparation method, and the grinding block is integral or spliced, wherein the spliced one is obtained by bonding with fillers.
[0034] The method for preparing the solid phase reaction grinding disc of the present invention comprises the following steps:
[0035] S1. Preparation of grinding block: The method for preparing the grinding block is the same as the method for preparing the grinding block described above;
[0036] S2 grinding disc bonding: the S1 solidified grinding block is bonded to a base disc having a certain shape to form a grinding disc;
[0037] S3. Dressing: Dress the surface of the grinding disc prepared in S2 to ensure the parallelism between the positioning surface of the grinding disc and the upper surface of the grinding disc and the flatness of the surface of the grinding disc.
[0038] The present invention also protects the use of a solid phase reaction grinding disk in grinding semiconductor wafers.
[0039] The semiconductor wafer described in the present invention is a wafer made of diamond, silicon carbide, sapphire, gallium nitride, indium phosphide, or gallium arsenide.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) The outer wall of the liquid marbles in the solid phase reaction grinding disc provided by the present invention is a hydrophobic nano-magnetic particle, which gives the liquid marbles a certain strength, ensuring that the marbles do not break during the mixing process and reducing the evaporation of the core liquid, while giving the liquid marbles excellent magnetic response performance. This performance can be used to control the movement of the liquid marbles through the magnetic field, prompting them to be oriented along the direction of the magnetic flux lines during the solidification process of the solid phase reaction grinding disc, thereby clamping and promoting the regularity of the directional distribution of the abrasive particles, which makes the grinding effect more consistent, the grinding efficiency improved, and the service life of the solid phase reaction grinding disc longer.
[0042] (2) When the solid-phase reaction grinding disc provided by the present invention is subjected to grinding processing, the liquid marbles will be broken due to mechanical action, which will reduce the holding force of the surface adhesive on the abrasive, causing the worn abrasive particles to fall off quickly, exposing new abrasive particles and liquid marbles, thereby improving the self-sharpening property of the solid-phase reaction grinding disc; at the same time, the reaction liquid and lubricating liquid released by the broken liquid marbles accelerate the solid-phase reaction rate, provide a liquid environment for the solid-phase reaction, and ultimately improve the material removal rate of the solid-phase reaction grinding disc; and the liquid marbles will form pits due to mechanical action, which can serve as a chip container, thereby solving the problem of easy clogging and wear of fine-grained bonded abrasive tools.
[0043] (3) The solid phase reaction grinding disc provided by the present invention does not need to rely on a large amount of reaction liquid and lubricating liquid dripped from the outside for grinding processing. Only the liquid marbles in the solid phase reaction grinding disc can realize the trace precise supply of reaction liquid and lubricating liquid, which reduces pollution and waste and complies with the principle of green manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a schematic diagram of the preparation process of the liquid marbles of the present invention.
[0045] Figure 2 It is a schematic diagram of the grinding block forming process under a vertical magnetic field of the present invention.
[0046] Figure 3 It is a schematic diagram of the grinding block forming process under the horizontal magnetic field of the present invention.
[0047] Figure 4 The overall structural schematic diagram of the integral solid phase reaction grinding disc bonded with the grinding block of the present invention.
[0048] Figure 5 A cross-sectional view of a monolithic solid phase reaction grinding disc bonded with the grinding block of the present invention.
[0049] Figure 6 The figure is a schematic diagram of the overall structure of the spliced solid phase reaction grinding disc bonded with the grinding block of the present invention.
[0050] Figure 7 The cross-sectional view of the spliced solid phase reaction grinding disc bonded with the grinding block of the present invention.
[0051] Figure 8 This is a schematic diagram of the processing flow of the liquid marble-type solid-phase reaction grinding disc provided by the present invention.
[0052] Fig. 9 The surface morphology and surface roughness of the sapphire wafer after grinding by the grinding block prepared in Example 1.
[0053] Fig.10 The surface morphology and surface roughness of the silicon carbide wafer after grinding by the grinding block prepared in Example 2.
[0054] Fig.11 The surface morphology and surface roughness of the gallium nitride wafer after grinding by the grinding block prepared in Example 3.
[0055] Among them, Figures 1 to 8 1 is a grinding block, 2 is a base plate, 3 is hydrophobic nano-magnetic particles, 4 is a reaction liquid or a lubricating liquid, 5 is abrasive grains, 6 is pores, 7 is a binder, 8 is a pellet, 9 is a filler, 10 is an upper mold, 11 is a mold sleeve, 12 is a lower mold, 13 is a permanent magnet, 14 is a hydraulic rod, 15 is the direction of force, 16 is the direction of magnetic flux lines, 17 is a semiconductor wafer, 18 is a solid phase reaction passivation layer, and 19 is grinding chips. DETAILED DESCRIPTION
[0056] The present invention will be further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Those skilled in the art will understand that the changes, replacements, and improvements made to the present invention still belong to the protection scope of the present invention. Unless otherwise specified, the raw material reagents used in the embodiments of the present invention are conventionally purchased raw material reagents.
[0057] Source of raw materials: Silica abrasive, ferroferric oxide abrasive, and diamond abrasive are produced by Shanghai Aladdin Reagent Co., Ltd., epoxy resin binder, magnesium oxychloride binder, ferroferric oxide nanomagnetic particles, nickel oxide nanomagnetic particles, magnesium fluoride powder, hydrogen peroxide reagent, and potassium hydroxide reagent are produced by Shanghai McLean Biochemical Technology Co., Ltd., sapphire wafers are produced by Jiangyin Haorui Optoelectronics New Materials Co., Ltd., SiC wafers are produced by Beijing Tianke Heda Blue Light Semiconductor Co., Ltd., and GaN wafers are produced by Beijing Beike New Materials Technology Co., Ltd.
[0058] Example 1
[0059] A solid phase reaction grinding block comprises the following components in parts by weight: 30 parts of abrasive, 60 parts of binder, and 25 parts of liquid marbles; the abrasive is silicon dioxide with an average particle size of 1 μm; the binder is epoxy resin; the particle size of the liquid marbles is 1 mm, including an outer wall and a core; the particle size of the liquid marbles is 1000 times the particle size of the abrasive; the outer wall of the liquid marbles is composed of hydrophobic nano-magnetic particles, and the core is liquid; the liquid marbles include first liquid marbles whose core liquid is a reaction liquid that can undergo solid phase reaction with the abrasive and second liquid marbles whose core liquid is a lubricating liquid; the hydrophobic nano-magnetic particles are ferrosoferric oxide particles with an average particle size of 16 nm; the reaction liquid is a magnesium fluoride-deionized water mixture, and the lubricating liquid is glycerol; wherein the first liquid marbles contain 15 parts of the liquid marbles and the second liquid marbles contain 10 parts of the liquid marbles; the liquid marbles and the abrasive in the grinding block are directionally arranged in the binder under the action of a magnetic field; the grinding block is integral.
[0060] The method for preparing the grinding block for solid phase reaction comprises the following steps:
[0061] S1. Evenly cover the surface of the culture dish with a layer of hydrophobic nano-Fe3O4 particles, extract 1mL of 15%wt magnesium fluoride-deionized water mixture and slowly dispense a drop of about 0.02mL of magnesium fluoride-deionized water mixture on the top of the culture dish, let the drop fall naturally into the culture dish, use a rubber-tipped dropper to move the drop so that the hydrophobic nano-Fe3O4 particles are evenly coated on the surface of the drop, and obtain the first liquid marble;
[0062] A layer of hydrophobic nano-Fe3O4 particles is evenly covered on the surface of the culture dish. 1 mL of glycerol is drawn and a drop of about 0.02 mL of glycerol is slowly dispensed on the top of the culture dish. The drop is allowed to fall naturally into the culture dish. A rubber-tipped dropper is used to move the drop so that the hydrophobic nano-Fe3O4 particles are evenly coated on the surface of the drop to obtain the second liquid marble. See the schematic diagram of the synthesis of liquid marbles for details. Figure 1 As shown, during the rolling process of the reaction liquid 4, the outer layer uniformly wraps the hydrophobic nano-magnetic particles to prepare liquid marbles.
[0063] S2. Grind, sieve and dry a certain amount of silica abrasive to remove moisture from the abrasive; drying conditions are: temperature 70°C, time 30min;
[0064] The first liquid marbles, the second liquid marbles and the silica abrasive prepared in S1 were mixed into the epoxy resin liquid, and 2% by mass of anhydrous ethanol was added and ultrasonically stirred at 20 kHz and at a constant speed for 20 minutes to obtain a mixed solution; wherein the mass ratio of the first liquid marbles to the second liquid marbles was 5.
[0065] After applying the release agent to the cavity wall of the mold, inject the mixed liquid while stirring at 20°C. Figure 2 As shown in the figure, an upper mold 10 is put on the cover, and permanent magnets 13 are placed at both ends of the upper mold 10 and the lower mold 12. A vertical magnetic field is applied, and the direction of the magnetic flux lines is vertical 16. The magnetic field strength is 100mT. After standing for 40 minutes, the mold is placed on a hydraulic press and pressure 15 is applied. The pressure size is 650N. After maintaining the pressure for 4 hours, the magnetic field and pressure are removed, and the mold is demoulded. After standing for 48 hours, a grinding block can be obtained, and the pores account for 15% of the volume of the grinding block.
[0066] Example 2
[0067] The difference from Example 1 is that a solid phase reaction grinding block includes the following components in parts by weight: 30 parts of abrasive, 50 parts of binder, and 25 parts of liquid marbles; the abrasive is ferroferric oxide with an average particle size of 5 μm; the binder is epoxy resin; the particle size of the liquid marbles is 2 mm, including an outer wall and a core; the particle size of the liquid marbles is 400 times the particle size of the abrasive particles; the outer wall of the liquid marbles is composed of hydrophobic nano-magnetic particles, and the core is liquid; the liquid marbles include a first reaction liquid in which the core liquid is a reaction liquid that can undergo a solid phase reaction with the abrasive The invention relates to a liquid marble and a second liquid marble whose core liquid is a lubricating liquid; the hydrophobic nano-magnetic particles are nickel oxide with an average particle size of 11 nm; the reaction liquid is a hydrogen peroxide solution, and the lubricating liquid is turbine oil; wherein the liquid marbles contain 15 parts of the first liquid marbles and 10 parts of the second liquid marbles; the liquid marbles and abrasives in the grinding block are directionally arranged in the binder under the action of a magnetic field; the grinding block is of a spliced type, wherein the pills and the filler are spliced together to form a whole grinding block, the pills are composed of abrasives, a binder and liquid marbles, and the filler is composed of a binder.
[0068] The method for preparing the grinding block for solid phase reaction comprises the following steps:
[0069] S1. Evenly cover the surface of the culture dish with a layer of hydrophobic nano-nickel oxide particles, draw 1 mL of 15% wt hydrogen peroxide solution and slowly dispense a drop of about 0.05 mL of hydrogen peroxide solution on the top of the culture dish, let the droplet fall naturally into the culture dish, use a rubber-tipped dropper to move the droplet so that the hydrophobic nano-Fe3O4 particles are evenly coated on the surface of the droplet, and obtain the first liquid marble;
[0070] A layer of hydrophobic nano-nickel oxide particles is evenly covered on the surface of the culture dish, 1 mL of turbine oil is drawn and a drop of about 0.05 mL of turbine oil is slowly dispensed on the top of the culture dish, and the droplet is allowed to fall naturally into the culture dish. A rubber-tipped dropper is used to move the droplet so that the hydrophobic nano-Fe3O4 particles are evenly coated on the surface of the droplet to obtain the second liquid marble.
[0071] S2. Grind, sieve and dry a certain amount of ferroferric oxide abrasive to remove moisture from the abrasive; drying conditions are: temperature 70°C, time 30min;
[0072] The first liquid marbles, the second liquid marbles and the ferroferric oxide abrasive prepared in S1 are mixed into the epoxy resin liquid, and anhydrous ethanol with a mass fraction of 2% is added, and ultrasonically stirred at 20kHz and at a constant speed for 20 minutes to obtain a mixed solution; wherein the mass ratio of the first liquid marbles to the second liquid marbles is 10;
[0073] After the mold cavity wall is coated with a release agent, the mixed liquid is injected at 20°C while stirring, and the upper mold is covered after the mixed liquid is injected. Magnets are placed at both ends of the upper and lower molds, and the magnetic field strength is 100mT. After standing for 40 minutes, the mold is placed on a hydraulic press and pressure is applied. The pressure is 200N. After maintaining the pressure for 4 hours, the magnetic field and pressure are removed, and the mold is demolded. After standing for 48 hours, a pill can be obtained. Several pills can be prepared by this method;
[0074] The pellets prepared in the above steps are placed in a mold in a concentric circle arrangement, and fillers are added to the remaining pores; after the fillers are injected, the upper mold is covered, and the mold is placed on a hydraulic press to apply pressure of 650N. After maintaining the pressure for 4 hours, the pressure is removed, the mold is demolded, and the grinding block is obtained. The pores account for 13% of the volume of the grinding block.
[0075] Example 3
[0076] The difference from Example 1 is that a solid-phase reaction grinding block includes the following components in parts by weight: 30 parts of abrasive, 60 parts of binder, and 25 parts of liquid marbles; the abrasive is diamond with an average particle size of 1 μm; the binder is a magnesium oxychloride binder; the particle size of the liquid marbles is 1 mm, including an outer wall and a core; the particle size of the liquid marbles is 1000 times the particle size of the abrasive; the outer wall of the liquid marbles is composed of hydrophobic nano-magnetic particles, and the core is liquid; the liquid marbles include first liquid marbles whose core liquid is a reaction liquid that can undergo a solid-phase reaction with the abrasive and second liquid marbles whose core liquid is a lubricating liquid; the hydrophobic nano-magnetic particles are ferroferric oxide particles with an average particle size of 16 nm; the reaction liquid is a potassium hydroxide solution, and the lubricating liquid is deionized water; wherein the first liquid marbles contain 15 parts of the liquid marbles and the second liquid marbles contain 10 parts of the liquid marbles; the liquid marbles and the abrasive in the grinding block are directionally arranged in the binder under the action of a magnetic field.
[0077] The method for preparing the grinding block for solid phase reaction comprises the following steps:
[0078] S1. Evenly cover the surface of the culture dish with a layer of hydrophobic nano-Fe3O4 particles, draw 1mL of 15% potassium hydroxide solution and slowly drop a drop of about 0.02mL of potassium hydroxide solution on the top of the culture dish, let the drop fall naturally into the culture dish, use a rubber-tipped dropper to move the drop so that the hydrophobic nano-Fe3O4 particles are evenly coated on the surface of the drop, and obtain the first liquid marble;
[0079] A layer of hydrophobic nano-Fe3O4 particles is evenly covered on the surface of the culture dish, 1 mL of deionized water is drawn and a drop of about 0.02 mL of deionized water is slowly dispensed on the top of the culture dish, and the droplet is allowed to fall naturally into the culture dish. A rubber-tipped dropper is used to move the droplet so that the hydrophobic nano-Fe3O4 particles are evenly coated on the surface of the droplet to obtain the second liquid marble.
[0080] S2. Grind, sieve and dry a certain amount of silica abrasive to remove moisture from the abrasive; drying conditions are: temperature 70°C, time 30min; wherein the mass ratio of the first liquid marbles to the second liquid marbles is 0.1;
[0081] The first liquid marbles, the second liquid marbles and the diamond abrasive prepared in S1 are mixed into the epoxy resin liquid, and 2% by mass of anhydrous ethanol is added, and the mixture is ultrasonically stirred at 20 kHz and at a constant speed for 20 minutes to obtain a mixed solution;
[0082] After applying the release agent to the cavity wall of the mold, inject the mixed liquid while stirring at 20°C. Figure 3 As shown, an upper mold 10 is placed on the cover, and permanent magnets 13 are placed on the left and right sides of the mold sleeve 11. A horizontal magnetic field is applied, the direction of the magnetic flux lines is horizontal 16, and the magnetic field strength is 100mT. After standing for 40 minutes, the mold is placed on a hydraulic press and pressure 15 is applied. The pressure size is 650N. After maintaining the pressure for 4 hours, the magnetic field and pressure are removed, the mold is demoulded, and the mold is stood for 168 hours to obtain a grinding block, in which the pores account for 5% of the volume of the grinding block.
[0083] Example 4
[0084] The difference from Example 1 is that the solid phase reaction grinding block includes the following components in weight proportions: 15 parts of abrasive, 45 parts of binder, and 15 parts of liquid marbles; the particle size of the liquid marbles is 5 mm; the particle size of the abrasive is 10 μm; the particle size of the liquid marbles is 500 times that of the abrasive; and the particle size of the hydrophobic nanomagnetic particles is 30 nm.
[0085] Example 5
[0086] The difference from Example 1 is that the solid phase reaction grinding block includes the following components in weight proportions: 20 parts of abrasive, 50 parts of binder, and 20 parts of liquid marbles; the particle size of the liquid marbles is 3 mm; the particle size of the abrasive is 15 μm; the particle size of the liquid marbles is 200 times that of the abrasive; and the particle size of the hydrophobic nanomagnetic particles is 50 nm.
[0087] Example 6
[0088] The difference from Example 1 is that the solid phase reaction grinding block includes the following components in weight proportions: 35 parts of abrasive, 50 parts of binder, and 20 parts of liquid marbles; the abrasive particle size is 20 μm; the liquid marble particle size is 100 times the abrasive particle size; and the hydrophobic nanomagnetic particle size is 100 nm.
[0089] Example 7
[0090] The difference from Example 1 is that the abrasive particle size in the solid phase reaction grinding block is 0.2 μm; the particle size of the liquid marbles is 10 μm; and the particle size of the liquid marbles is 50,000 times the particle size of the abrasive particles.
[0091] Example 8
[0092] The difference from Example 1 is that the abrasive grain size in the solid phase reaction grinding block is 30 μm; and the particle size of the liquid marbles is 66.7 times that of the abrasive grain size.
[0093] Comparative Example 1
[0094] The difference from Example 1 is that the liquid marbles in the grinding block of the solid phase reaction are only composed of the first liquid marbles of the magnesium fluoride-deionized water reaction solution.
[0095] Comparative Example 2
[0096] The difference from Example 1 is that the liquid marbles in the grinding block of the solid phase reaction are composed only of glycerol lubricating liquid and second liquid marbles.
[0097] Liquid marble strength test
[0098] The liquid marbles obtained in Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to strength tests, and the test results are shown in Table 1. In Table 1, "pass" means that the liquid marbles prepared in Examples 1 to 8 and Comparative Examples 1 to 2 hit the glass plate at a speed of 0.8 m / s when they were freely dropped from a height of 30 mm, and the liquid marbles did not break. Such strength of the liquid marbles ensures that the liquid marbles will not break during the mixing process, but will break during the grinding process.
[0099] Table 1 Liquid marble strength test results obtained from Examples 1 to 8 and Comparative Examples 1 to 2
[0100]
[0101] Preparation of grinding disc:
[0102] S1. Grinding disc bonding: bonding the cured grinding block to a base disc having a certain shape to form a grinding disc; the grinding disc is from any one of Examples 1 to 8 or Comparative Examples 1 to 2.
[0103] S3. Finishing: Use fine-grained sandpaper to grind the bonding surfaces of the base disc and the grinding block, then apply 504AB glue on the bonding surfaces, bond the base disc and the grinding block, compact them, and dry them in an oven at 30°C for 20 hours to obtain the grinding disc; after the grinding disc is made, turn the upper surface of the grinding disc on a horizontal lathe to ensure the parallelism between the positioning surface of the grinding disc and the upper surface of the grinding disc and the flatness of the surface of the grinding disc.
[0104] The prepared grinding disc is divided into an integral structure grinding disc and a spliced structure grinding disc according to the structure of the grinding block; the overall structure of the integral grinding disc is as follows Figure 4 Its cross-sectional structure is shown in Figure 5 As shown, the grinding block 1 is bonded to the base plate 2, and the grinding block 1 is uniformly distributed with hydrophobic nano-magnetic particles 3, reaction liquid or lubricating liquid 4, abrasive particles 5, pores 6, and adhesive 7, which together constitute the whole of the grinding block 1. The overall structure of the spliced grinding disc is as follows Figure 6 Its cross-sectional structure is shown in Figure 7 As shown, the grinding block 1 is bonded to the base plate 2, and the pellets 8 are evenly distributed with hydrophobic nano-magnetic particles 3, reaction liquid or lubricating liquid 4, abrasive particles 5, pores 6, and adhesive 7. The pellets 8 and fillers 9 splice the grinding block together to form a whole grinding block.
[0105] Performance Testing
[0106] The solid phase reaction grinding disc was used to perform semiconductor wafer processing experiments on a KD15BX single-sided grinding machine, with a grinding pressure of 10-15 kPa and a rotation speed of 70-200 r / min. After 60 minutes of processing, the surface morphology and surface roughness of the semiconductor wafer after grinding were detected using a white light interferometer. The test results of the grinding effects of the grinding blocks prepared in Examples 1-8 and Comparative Examples 1-2 on semiconductor wafers are shown in Table 2. The surface roughness of the semiconductor wafer after grinding by the grinding blocks prepared in the Examples is significantly less than the roughness of the semiconductor wafer after grinding by the grinding blocks prepared in the Comparative Examples.
[0107] Figure 8 The schematic diagram of the process of grinding a sapphire wafer by the grinding block prepared in Example 1 is as follows: under the action of friction, the silica abrasive in the grinding disk reacts with the sapphire wafer in a solid phase reaction to generate mullite with a lower hardness, and a softer passivation layer is formed on the surface of the sapphire wafer; the liquid marbles distributed around the silica abrasive are broken due to mechanical action, wherein the magnesium fluoride-deionized water mixture is used as a solid phase reaction catalyst to increase the reaction rate, and industrial glycerin is used as a lubricant to make the grinding more uniform; under the action of friction, the passivation layer is removed by the silica abrasive, and the grinding debris and the remaining hard large particles are trapped in the cavities of the broken liquid marbles, avoiding the problem of clogging and wear, and the surface of the new sapphire wafer is exposed, and the above processing steps are repeated to obtain a sapphire wafer with a small surface roughness and smooth surface. Fig. 9 The solid phase reaction grinding disc is used to process the surface morphology and surface roughness of a sapphire wafer. Figure 8 same.
[0108] The solid phase reaction process is as follows:
[0109]
[0110] Fig.10 The surface morphology and surface roughness of the silicon carbide wafer after grinding by the grinding block prepared in Example 2. The principle of processing silicon carbide wafers using the solid phase reaction grinding disc is as follows: under the action of friction, the liquid marbles distributed around the ferroferric oxide abrasive are broken by mechanical action, and the released hydrogen peroxide solution generates highly oxidizing hydroxyl radicals under the catalytic action of ferrous ions in ferroferric oxide, which oxidize the silicon carbide wafer to form a soft oxide layer, which is then removed by the abrasive.
[0111] The solid phase reaction process is as follows:
[0112] Fe 2+ +H2O2→Fe 3+ + OH+OH -
[0113] Fe 3+ +H2O2→Fe 2+ +H + + OOH
[0114] SiC+4·OH+O2→SiO2+2H2O+CO2↑
[0115] Fig.11 The surface morphology and surface roughness of the gallium nitride wafer after grinding by the grinding block prepared in Example 3. The principle of using the solid phase reaction grinding disc to process gallium nitride wafers is as follows: under the action of friction, the liquid marbles distributed around the diamond abrasive are broken by mechanical action, and the released potassium hydroxide solution can be used as a catalyst for the solid phase reaction between gallium nitride and deionized water. Each nitrogen atom on the surface nitrogen end layer of gallium nitride has a negatively charged suspension layer. Under the catalytic action of potassium hydroxide, hydroxide ions are adsorbed on the negatively charged suspension layer to form gallium oxide and ammonia, and the gallium oxide can be removed by the diamond abrasive.
[0116] The solid phase reaction process is as follows:
[0117]
[0118] Table 2 Surface roughness of polished semiconductor crystal sheets of the grinding blocks prepared in Examples 1 to 8 and Comparative Examples 1 to 2
[0119]
[0120] According to the results of the surface roughness of the polished semiconductor crystal pieces of the grinding blocks prepared by Examples 1 to 8 and Comparative Examples 1 to 2 in Table 1, it can be seen that: in Examples 1, 2, and 5, as the abrasive particle size increases, the roughness of the ground semiconductor wafer increases; in Examples 1, 4, and 6, as the liquid marble particle size decreases relative to the abrasive particle size, the roughness of the ground semiconductor wafer increases. This is because in the process of grinding semiconductor wafers, the abrasive or reaction liquid and the semiconductor wafer undergo a solid-phase reaction due to friction to form a passivation layer, and the liquid marbles arranged in a direction near the abrasive are broken under the action of mechanical force, and the liquid inside is gradually released, wherein the reaction liquid plays a role in accelerating the solid-phase reaction rate, and the lubricating liquid plays a role in making the grinding more uniform. The reaction liquid and the lubricating liquid together provide a liquid environment for the solid-phase reaction, accelerating the solid-phase reaction rate. In comparison example 1, only the first liquid marbles are present but the second liquid marbles are not added. Therefore, there is a lack of lubricating liquid during the wafer grinding process, and uniform grinding cannot be achieved. In comparison example 2, only the second liquid marbles are present but the second liquid marbles are not added. Therefore, there is a lack of reaction liquid during the wafer grinding process, the solid-phase reaction rate is slowed down, and a sufficient passivation layer cannot be generated, so the surface of the crystal sheet cannot be effectively ground to reduce its roughness.
[0121] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A solid phase reaction grinding block, characterized in that: The solid phase reaction grinding block comprises the following components in parts by weight: 15 to 35 parts of abrasive, 45 to 60 parts of binder, and 15 to 25 parts of liquid marbles; the solid phase reaction grinding block also comprises pores distributed inside the solid phase reaction grinding block; The liquid marbles and abrasives in the solid phase reaction grinding block are directionally arranged in the binder; the abrasive particle size is 0.2μm~30μm, the liquid marble particle size is 10μm~5mm, and the liquid marble particle size is ≧20 times the abrasive particle size; the liquid marbles include a core and an outer wall; the outer wall of the liquid marbles is composed of hydrophobic nanomagnetic particles, and the core is liquid; the liquid marbles include a first liquid marble whose core liquid is a reaction liquid that can undergo a solid phase reaction with the abrasive and a second liquid marble whose core liquid is a lubricating liquid; the mass ratio of the first liquid marble to the second liquid marble is 0.1~10.
2. The solid phase reaction grinding block according to claim 1, characterized in that: The abrasive is a soft abrasive or a hard abrasive.
3. The solid phase reaction grinding block according to claim 2, characterized in that: The soft abrasive is one or more of silicon dioxide, cerium oxide, and silica sol, and the hard abrasive is one or more of diamond, silicon carbide, and aluminum oxide.
4. The solid phase reaction grinding block according to claim 1, characterized in that: The binder is one or more of a phenolic resin binder, a polyimide resin binder, an epoxy resin binder, and a magnesium oxychloride binder.
5. The solid phase reaction grinding block according to claim 1, characterized in that: The hydrophobic nano magnetic particles are one or more of ferroferric oxide, carbonyl iron powder, nickel oxide, manganese ferrite, cobalt ferrite and nickel ferrite magnetic powder.
6. The solid phase reaction grinding block according to claim 1, characterized in that: The reaction liquid is one or more of a magnesium fluoride solution, a boron oxide solution, a Fenton reaction liquid, and an ultraviolet photocatalytic reaction liquid.
7. The method for preparing the solid phase reaction grinding block according to any one of claims 1 to 6, characterized in that: The steps include: S1. Add the reaction liquid and the lubricating liquid dropwise onto the hydrophobic nanomagnetic particle layer, saturate the hydrophobic nanomagnetic particles and wrap them on the droplets to form liquid marbles on the droplets; S2. Mix the ground, sieved and dried abrasive, binder and liquid marbles prepared in S1 in proportion, inject the mixture and apply magnetic field and pressure on the upper and lower surfaces of the mold in sequence, and demold the grinding layer after solidification at room temperature; the magnetic field strength is 20~800mT, and the pressure is 50~1000N.
8. A solid phase reaction grinding disc, characterized in that: It comprises the solid phase reaction grinding block as described in any one of claims 1 to 6, wherein the solid phase reaction grinding block is bonded to a base plate.
9. Use of the solid phase reaction grinding disc according to claim 8 in grinding semiconductor wafers.
10. The use according to claim 9, characterized in that: The semiconductor wafer is a wafer made of diamond, silicon carbide, sapphire, gallium nitride, indium phosphide or gallium arsenide.
Citation Information
Patent Citations
Abrasive particle oriented solid-phase reaction grinding disc suitable for SiC wafer and preparation method and application of abrasive particle oriented solid-phase reaction grinding disc
CN113118967A
SiC single crystal wafer polishing method
CN113524025A